2016
DOI: 10.1021/acs.est.6b00605
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium(IV) and (V) Sorption to Goethite at Sub-Femtomolar to Micromolar Concentrations: Redox Transformations and Surface Precipitation

Abstract: Pu(IV) and Pu(V) sorption to goethite was investigated over a concentration range of 10(-15)-10(-5) M at pH 8. Experiments with initial Pu concentrations of 10(-15) - 10(-8) M produced linear Pu sorption isotherms, demonstrating that Pu sorption to goethite is not concentration-dependent across this concentration range. Equivalent Pu(IV) and Pu(V) sorption Kd values obtained at 1 and 2-week sampling time points indicated that Pu(V) is rapidly reduced to Pu(IV) on the goethite surface. Further, it suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 52 publications
(158 reference statements)
0
24
0
1
Order By: Relevance
“…Unfortunately, for analytical convenience, most laboratory Pu-NOM interaction experiments are often performed at Pu concentrations that greatly exceed those observed in contaminated environments, and the results are then simply extrapolated to ambient environmental conditions. However, this assumption may be unrealistic due to the availability of limited surface-mediated oxidation-reduction reactions sites and strong Pubinding sites, and Pu (IV) tends to form polymeric or colloidal Pu-oxide particles (i.e., intrinsic colloids) at higher concentrations (Zhao et al, 2016) The strategy to resolve this issue is to use a suites of techniques including solvent extraction, ultrafiltration, radiolabelling and isoelectric focusing (IEF) electrophoresis, followed by alpha-counting or ICP-MS determination to obtain natural organic macromolecules that are complexing and immobilizing/remobilizing Pu (Figs. 4a and 4b, also see Xu et al, 2008Xu et al, , 2015bXu et al, , 2016.…”
Section: Characterizing Pu-nom Interactions At Ambient Concentrationsmentioning
confidence: 99%
“…Unfortunately, for analytical convenience, most laboratory Pu-NOM interaction experiments are often performed at Pu concentrations that greatly exceed those observed in contaminated environments, and the results are then simply extrapolated to ambient environmental conditions. However, this assumption may be unrealistic due to the availability of limited surface-mediated oxidation-reduction reactions sites and strong Pubinding sites, and Pu (IV) tends to form polymeric or colloidal Pu-oxide particles (i.e., intrinsic colloids) at higher concentrations (Zhao et al, 2016) The strategy to resolve this issue is to use a suites of techniques including solvent extraction, ultrafiltration, radiolabelling and isoelectric focusing (IEF) electrophoresis, followed by alpha-counting or ICP-MS determination to obtain natural organic macromolecules that are complexing and immobilizing/remobilizing Pu (Figs. 4a and 4b, also see Xu et al, 2008Xu et al, , 2015bXu et al, , 2016.…”
Section: Characterizing Pu-nom Interactions At Ambient Concentrationsmentioning
confidence: 99%
“…Since the 1940’s, worldwide Pu inventory has evolved from almost 0 to ~2,500,000 kg due to anthropogenic activities 33,34 , and is estimated to increase by 70,000 kg/year 35 based on civilian nuclear power generation forecasts. Pu materials must be properly safeguarded throughout their lifespan, which necessitates advanced nuclear forensic controls and reprocessing activities.…”
Section: Resultsmentioning
confidence: 99%
“…The plutonium sorption is complicated by redox reactions; hence, this topic remains open for discussion and study (Romanchuk et al, 2016b ). Recently, it was found that Pu(IV) stabilization onto mineral surfaces may result in Pu surface precipitation in the form of PuO 2 nanoparticles (Kirsch et al, 2011 ; Romanchuk et al, 2013 , 2016a ; Schmidt et al, 2013 ; Zhao et al, 2016 ) ( Figure 2 ). Therefore, the study of PuO 2 nanoparticles becomes increasingly important, and it is actively being conducted (Powell et al, 2011 ; Romanchuk et al, 2018 ; Kvashnina et al, 2019 ; Gerber et al, 2020 ).…”
Section: Plutoniummentioning
confidence: 99%